(untitled) (Metallurgy and Foundry Engineering, 2012)
Reduction of CO2 emission can be achieved in metallurgical processes. Unit, which has high potential for reducing CO2 emission is a blast furnace, where after the separation of CO2 from the top gas, this gas can be recycled. Gained CO2 can be used in steelmaking processes. Paper shows the results of CO2 blowing into molten metal in order to oxidize carbon and silicon.